EDUKASI MANAJEMEN KEUANGAN RUMAH TANGGA UNTUK KELANJUTAN USAHA BAGI UMKM JAWARA DEPOK - Alya Budiantini; Aat Sutihat; Fitriyah (Publika Citra Media, 2026)
Research and Community Service (PKM) is one of the manifestations of the Tri Dharma of Higher Education. The purpose of the PKM activity is to foster lecturers in improving their abilities, skills, and independence as well as the existence of Pamulang University as an agent of change in order to provide significant benefits to the community. This time the Unpam Accounting Study Program held PKM at UMKM Jawara Depok. The purpose of the activity is to provide financial management eeduaction in managing household finances for the sake of the continuaity of Msme businesses in the future so that it is hoped that economic prosperity will be achieved. The Importance of this activity is due to economic instability and increased knowledge of financial management that is managed and educated the community, to manage household finances well and optimally and skills in financial management can be applied in everyday life as provisiaons in the future. The implementation of PKM Consists of Psesntatins of materials, discussions and training at the enda of the session to determine the extent to whicg the material has been absorbed. A question and answae session was held with UMKM Jawara Depok.